PENGEMBANGAN BAHAN AJAR SUBTEMA INDAHNYA KERAGAMAN BUDAYA DINEGERIKU UNTUK MENINGKATKAN KARAKTER CINTA TANAH AIR PADA SISWA KELAS IV SD - Nella Audina Kusuma Citra; Alfi Laila; Rian Damariswara (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The background of this research is the observation that 30% of students KKM and 70% KKM, students who are less disciplined in doing and collecting assignments, speak impolitely, do not care about the troubles of their friends. The aims of this study are (1) to determine the validity, practicality and effectiveness of the product development of teaching materials for students with the sub-theme of the beauty of cultural diversity in my country to improve the character of love for the homeland in fourth grade elementary school students in the 2020/2021 academic year? Research and development (research and development) ADDIE model. Subjects 40 students. The research site is Lirboyo 2 Elementary School, Kediri City. Statistical analysis analysis techniques. It was concluded that: 1) The validity of the product development of student teaching materials with the sub-theme of the beauty of cultural diversity in my country to improve the character of love for the homeland in students, with a score of 92-96. 2) The effectiveness of the product development of student teaching materials with the sub-theme of the beauty of cultural diversity in my country to improve the character of love for the homeland in students, with the average score of student test results being 83.12 > 75 above the KKM. 2) The practicality of product development of student teaching materials with the sub-theme of the beauty of cultural diversity in my country to improve the character of love for the homeland in students, with a score of 88.